The Impact of Mobility and Migration on Health-Related Risk and Vulnerability Among People Who Use Drugs in Ottawa-Gatineau - Schreiber, Yoko S. (Université d'Ottawa / University of Ottawa, 2014)
Migration and mobility processes are thought to be important (yet complex) modulators of health related risk and vulnerability as experienced by people who use drugs. Few studies in Canada have examined this relationship, and there is no research available addressing this specific aspect of health and well-being in people who use drugs in Ottawa-Gatineau. While migration can be defined as a permanent (or near permanent) relocation process, mobility refers to a person's temporary or short-term movement between geographic locations (Joint United Nations Programme on HIV/AIDS, 2001). Understanding how the reasons for mobility and migration, typically described as “push and pull” factors, and the processes itself impact on the local community is invaluable for informing intervention in terms of type, location and timing and identifying solutions to reduce the inequalities resulting in and from the migration process. This cross-sectional study aimed to assess the prevalence and geography of mobility and migration among study participants, characterize the circumstances surrounding the mobility and migration process, and explore their impact on health related outcomes, among people who use drugs in Ottawa-Gatineau, Canada. Understanding the prevalence, patterns and characteristics of mobility and migration events may offer greater insight into the associated health risks, which in turn will assist in the development of targeted health and social services for this group. We hypothesized that the act of moving itself, as well as type of mobility and migration (i.e. specific push and pull factors), may be associated with health risk behaviours and health outcomes. People 18 years or older currently living in Ottawa-Gatineau, and who used illicit drugs in the past six months were recruited using respondent-driven sampling. Geography of lifetime migration was mapped, and health related outcomes and access to social support services were evaluated against lifetime and recent migration and travel. Quantitative analysis of health and social support related outcomes was carried out by comparison of means and proportions between groups, and complemented by qualitative exploration of push and pull factors and effects of the last mobility and migration events. Our study identified a heterogeneous inner-city population of people who use drugs where widespread homelessness, incarceration, low income and a high degree of mobility and migration placed individuals at varying levels of health-related vulnerability. Participants moved to Ottawa-Gatineau from all over Canada and other countries, but most arrived from within Ontario. Multiple factors were involved in the decision to migrate and in choosing Ottawa-Gatineau in particular. Escaping a negative environment and seeking out family connections were the most commonly cited “push and pull” factors, respectively. Maintaining family connections was also identified as a major reason for mobility or lack thereof among travelers and non-travelers alike. There was evidence to suggest that the mobility and migration processes affected health, drug use and access to resources among some of the participants and for a wide variety of reasons. Comparing the two groups using t-test for means and Chi-square (or Fisher’s exact) test for proportions, we found crack cocaine and injection drug users who migrated recently to be poorly connected to harm reduction services and thus at particularly high risk for blood-borne infections and other drug-related harms. Similarly, participants using crack cocaine or injection drugs and who traveled were significantly less likely to access social support services. In this study we have shown that within a broad cohort of people who use drugs in Ottawa-Gatineau, subjects are a highly mobile group, and face a considerable number of environmental challenges that predispose individuals to increasing risk behaviour even when using drugs only occasionally. This vulnerability is greatest in the period following migration. While push and pull factors may vary by place, a common theme identified in this study is the perceived and actual positive influence of family. Further research employing a combination of quantitative and qualitative methods using a socioecological, intersectionality and lifecourse approach (Egan, et al., 2011) may provide added insights into the role of family in modulating vulnerability through social connectedness and support among drug users as they navigate the mobility and migration process.
Keywords: mobility; migration; IDU; health-related vulnerability